Isolamento, caracterização e perfil de resistência de salmonella spp. isoladas de cortes de frangos - Silva, Ana Carolina Pereira da (2020)
Chicken is an animal protein most consumed in Brazil, which is a leader in the world ranking of exports of this food. Its high consumption must be low price and high nutritional value, however, it is a vehicle for pathogenic microorganisms such as Salmonella spp. Antimicrobial agents have been used in agriculture for many years to control the proliferation of these microorganisms and this favored prolonged stay or surgery of resistance mechanisms in strains of Salmonella spp. Therefore, the aim of the present study was to isolate and characterize Salmonella spp. from cuts of chickens marketed in the city of Francisco Beltrão - Paraná and verify the front resistance profile for antimicrobials used in human medicine. 40 samples of chicken cuts were purchased from supermarkets in Francisco Beltrão - PR. The microbiological analyzes followed the stages of preenrichment, selective enrichment and differential plating. The suspected colonies were subjected to biochemical tests carried out in a Kit for the identification of enterobacteria (NEWPROV). Four colonies from each sample were selected with Salmonella spp. biochemical behavior, totaling 28 isolates, to perform the antimicrobial sensitivity test. Samples that showed resistance to ceftriaxone were subjected to extended spectrum beta lactamases. All isolates subjected to antimicrobial susceptibility testing demonstrated sensitivity to meropenem, whereas 100% of the isolates were resistant to nalidixic acid, a high resistance to beta lactam antimicrobials was also observed. Seventeen different resistance profiles were found, with 42.85% showing a multi-resistance profile and 21.42% of the isolates showing a phenotype for ESBL production. The frequency of batches contaminated with Salmonella spp. of 17.5% in chicken cuts destined for commercialization, points to the importance of proper cooking and handling of these foods for the prevention of salmonellosis outbreaks. The high resistance to antimicrobials and their potential for dissemination found in this study is a worrying fact, as it puts at risk the treatment of infections caused by Salmonella spp.